Ühe varauusaegse hauatähise retoorika: kriitika, korrektiivid ja uued hüpoteesid - Varik, Veikko (Usuteaduslik Ajakiri, 2022)
The Rhetoric of an Early Modern Tombstone: Criticisms, Corrections, and New Hypotheses. The Baron Pontus de la Gardie monument (after 1589–1593) is the first such magnificent early modern work of memorial art dedicated to the memory of a nobleman not belonging to the royal family, not only in Estonia, but apparently in the entire area under the authority of the Swedish crown. Until now, the Gustav Vasa monument in Uppsala has been considered as its example, and more indirect examples have been sought in the Netherlands, Germany and France. The research showed that there is reason to look at the details of all the monuments of the members of the Swedish royal family erected in the Uppsala Cathedral to the end of the 1580s as the closest ideal examples. The arquitectonic and design elements of the monuments, even the use of some materials, point to the interrelationships of Tallinn tombstone and Uppsala monuments. Beside this there is a reason to look for examples of relief details mainly in the Netherlands. Johan Vredeman de Vrie, Jakob Floris and Maarten de Vos must be mentioned as the main authors of the exemplary engravings. In the course of the study, based on a qualitative content analysis focused on the manifest part of the content, a more complete picture of the iconography used on the monument, the connections of its different layers and interaction with the verbal text of the monument was obtained. The orders and directions of "reading" established by the designer of the monument were also revealed, which confirmed some earlier hypotheses, but also brought up a number of points of view worthy of criticism, e.g. for example, about the overwhelming Lutheranism of the monument, but also about the message of the images. The last, but by no means the least important, must be mentioned the identification of facts that shed new light on the history of the formation of this grave marker. The factology found allows us to hypothesize that both Johan III and Willem Boy were involved in designing the monument. The latter makes it possible to place de la Gardie’s monument in the context of the memorial art of the late 16th century in the Kingdom of Sweden.